Potencial de morse como perfil de pozos cuánticos semiconductores (2016)
ABSTRACT: Theoretical calculations of the energy and wave function of the ground state and the first excited state of an electron confined in a GaAsAl/GaAs quantum well with Morse-like potential profile are presented using the effective mass approximation method and the envelope wave function. The inter-sub-band transitions according to the parameters defining the geometry of the Morse potential, to represent the inter-diffusion between materials of the barrier and the well, are analyzed. Additionally, are shown the peaks of the nonlinear optical rectification as a function of energy of incident photons and its resonance with the transition energy between the two states. An electric field is applied in the growth direction of the quantum well and a magnetic field perpendicular to the heterostructure in order to study the shifts of the optical response peaks in the spectrum of the incident photons.